What is Important? The Impact of Interpersonal Political Discussion on Public Agendas1. (5th December 2012) - van, Bas W.
<x xml:space="preserve">Abstract</x> Objective This article investigates the role of discussion networks in agenda‐setting. More specifically, the focus is on the question whether the partisan composition of people's discussion networks affects what they judge to be the most important problems facing the country. Method Using data from the 2000 American National Election Studies (ANES), I employ logistic regression analysis. Results The findings suggest that discussion networks indeed play a significant role in setting the public agenda, even taking into consideration people's media use and several other potentially relevant variables. Conclusion While prior research has already linked political discussion to participation and vote choice, this study provides evidence that it also affects what issues people prioritize.